Capillary film and breakup mechanism in the squeezing to dripping transition regime at the mesoscale between micro and milli-fluidics - Freytes, Verónica Mariana (2018)
We report a study of droplet generation in two phase flows of non-miscible fluids in a T-shaped array of circular channels, at the mesoscale between micro- and milli-fluidics. Our experiments show that the balance between the different types of forces (capillary forces, shear viscous forces, etc.) may differ significantly from that found by previous authors in smaller, microfluidics channels. The results may, therefore, be applied to practical systems in which droplets act as small chemical reactors or help enhance mixing. We suggest a possible interesting extension to the generation of drops inside porous media. We report experiments in which the length of the droplets and the residual thickness of the surrounding fluid film are systematically measured as a function of the respective flow rates of the two fluids: These results are carefully compared to theoretical models taking into account in different ways the capillary and viscous effects and to results obtained by other authors for smaller channels. Several dimensionless control variables are tested (capillary number, ratio of the flow rates of the two fluids, etc.). Capillary film thickness is shown to be a useful variable to identify the different regimes of formation. Testing of the theoretical models with the experimental data showed that the change from one formation regime to the other is accompanied by a change in the role of viscous effects. Two models of breakup mechanisms were tested: on the one hand, the pressure buildup mechanism and, on the other hand, a second mechanism corresponds to the balance of tangential shear stresses and interfacial tension. According to the formation regimes, both models have provided satisfactory predictions of the experimental results. However, at this mesoscale, the experimental data were better described by the models dependent on the capillary number, as previously reported in systems with a low degree of confinement.